The Hierarchychal Leadership in Sufi Order: Duties and Positions of Imam Khususi - Masyhar, Aly; Abdul Djamil (Indonesian Journal of Islamic Literature and Muslim Society, 2021)
This article elaborates on the hierarchy in Tariqa Qadiriyahwa Naqsyabandiyah al-Usmaniyah (TQN al-Usmaniyah) in Kedinding, Surabaya. This study investigates the history, task, and position of Imam Khususi. Besides, this article also explores the similarity and differences between Imam Khususi in various Tariqa of TQN of various terms. The significance of this study deals with the term Imam Khususi as one of the positions of a leader in the hierarchy in TQN turns out to be strange for other TQN orders, especially for TQN Mranggen and TQN Magelang. The findings of this study describe that (1) the term Imam Khususi as one of the positions in hierarchical leadership in TQN was first introduced by KH. ‘Utsman, (2) the position of Imam Khususi is between murshid and murid, and the task is to help murshid in leading Majelis Khususiyah, and (3) Imam Khususi has a similar position as caliph sugra in TQN Mranggen dan it is also similar as badal in TQN Berjan or many others TQN which get irsyad license from TQN Mranggen.